2019
DOI: 10.1007/978-3-030-11286-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Mining Actionable Information from Security Forums: The Case of Malicious IP Addresses

Abstract: The goal of this work is to systematically extract information from hacker forums, whose information would be in general described as unstructured: the text of a post is not necessarily following any writing rules. By contrast, many security initiatives and commercial entities are harnessing the readily public information, but they seem to focus on structured sources of information. Here, we focus on the problem of identifying malicious IP addresses, among the IP addresses which are reported in the forums. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Interestingly as we showed in our first research [4,5], not all of the reported IP addresses are malicious, which makes the classification necessary. It turns out that this is a two-step problem.…”
Section: Introductionmentioning
confidence: 83%
“…Interestingly as we showed in our first research [4,5], not all of the reported IP addresses are malicious, which makes the classification necessary. It turns out that this is a two-step problem.…”
Section: Introductionmentioning
confidence: 83%
“…As attackers, users visit security-community websites to share security/hacking knowledge and even sell stolen data after unauthorised intrusions into other systems [16,17]. As defenders, users participate in security web channels to identify hacking information or improve the security of computer systems [18,19]. In reality, [20] found that, on average, 53% of security-community users use and sell malicious services.…”
Section: Online Community and Cyber-security Communitymentioning
confidence: 99%